2016
DOI: 10.1097/ajp.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tailored Positive Psychology Intervention on Well-Being and Pain in Individuals With Chronic Pain and a Physical Disability

Abstract: The results support the feasibility, acceptability, and potential efficacy of a computer-based positive psychology intervention for improving well-being and pain-related outcomes in individuals with physical disabilities and chronic pain, and indicate that a full trial of the intervention is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 84 publications
(92 reference statements)
8
134
0
Order By: Relevance
“…Such interventions could include web-based learning programs that teach simple well-being exercises and that require few resources to maintain once they are established (eg, Ref. 45). Clinicians who interact with these individuals when providing basic or general health care could be taught strategies that could enhance pain acceptance, such as pain neuroscience education interventions (eg, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions could include web-based learning programs that teach simple well-being exercises and that require few resources to maintain once they are established (eg, Ref. 45). Clinicians who interact with these individuals when providing basic or general health care could be taught strategies that could enhance pain acceptance, such as pain neuroscience education interventions (eg, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…A recent feasibility study suggests that other interventions focused on building assets may also be of benefit to people with chronic pain. Muller et al (2015) evaluated the effects of a web-based positive psychology intervention for chronic pain, which was designed in part to increase positive affect, and found that it not only improved positive affect but also pain-specific outcomes, including pain intensity, pain interference, and mood post-treatment, with the effects on pain intensity, mood, and pain control maintained at a 2.5 month follow-up. Even though they are not typically conceptualized as building assets as much as they are thought to address maladaptive behaviors and thoughts, traditional behavioral therapies for chronic pain, including CBT, may also increase resilience factors and should be studied for such benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions have attempted to encapsulate traditional positive psychological approaches by targeting mechanisms that bolster positive emotional states and improve social relations. These activities may include exercises that promote forgiveness of others for prior harms, sharing of gratitude with supportive others, promoting prosocial behaviors (e.g., performing random acts of kindness), cultivating compassion toward the self and others, savoring positive experiences, enhancing optimism and pursuing personally meaningful goals [78,79]. These interventions constitute a promising step away from treating pain using strictly a problem-focused approach and instead promoting overall health and meaningful function.…”
Section: Future Directions For Studymentioning
confidence: 99%